A Statistical-based Stability-Indicating Assay for the Estimation of Salbutamol and Ketotifen using HPLC and HPTLC Methods - Ghosh, Manik; Bandewar, Reetu; Mondal, Arijit; Dey, Suddhasattya; Sarkar, Saptarshy; Behera, Padma Charan; Jha, Sajal Kumar; Mandal, Sudip Kumar (Current Spectroscopy and Chromatography, 2024)
BackgroundThere are very few methods for simultaneously determining a combined dose of SAL and KET.ObjectivesThe current study aims to explore accurate, precise, simple, and cost-effective HPLC and HPTLC techniques for the simultaneous assessment of Salbutamol (SAL) and Ketotifen (KET).MethodsThe determination of Salbutamol and Ketotifen was performed by HPLC and HPTLC methods using 280 nm and 258 nm as the determination wavelength, respectively. Methanol was used to dissolve the drug for estimation in HPLC using mobile phase methanol: 10mM di-Potassium hydrogen orthophosphate in the ratio of 55:45 v/v of pH 4 at a flow rate of 1mL/min and in chloroform: toluene: methanol (7: 2: 3 v/v/v) for the estimation in HPTLC. Moreover, a statistical comparison was made between the results obtained through HPLC and HPTLC of Salbutamol (SAL) and Ketotifen (KET) using the Student’s t-test and F-test.ResultsA linear response was observed in the range of 4-24 µg/mL and 2-12 µg/mL, respectively, for SAL and KET for HPLC. R2 was found to be 0.9998 and 0.9999, respectively. For HPTLC, the linear response was observed in the concentration range of 20-120 ng/ spot and 10 - 60 ng/ spot for SAL and KET, respectively. R2 was found to be 0.9988 and 0.9998, respectively. The limit of detection (LOD) for HPLC was estimated as 0.34 µg/ml and 0.10 µg/ml for SAL and KET, respectively, and for the HPTLC method, the LOD was estimated as 4.8 µg/ml and 1.5 µg/ml, respectively. Analysing the marketed formulation by using both methods, SAL and KET within the range of 100 ± 2% were recovered. The results obtained after the estimation of the Mastifen S tablet by applying both methods were according to nominal content. Degradation studies were performed using both methods. It was found that Salbutamol was unstable in hydrolytic, oxidative and thermal degradation, whereas stable in photolytic conditions. Ketotifen was found to be stable in thermal and photolytic conditions and unstable in hydrolytic and oxidative conditions.ConclusionThe proposed stability indicating HPLC and HPTLC methods for SAL and KET was found to be simple, accurate, and reproducible for quantitative estimation in pharmaceutical dosage form, without interference from the excipients or degradation products from the main drug component.
Keywords: HPLC